Keefektifan Cara Belajar Berkelompok dalam Pembelajaran Matematika - Qamaruddin Qamaruddin (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Effectiveness of Group Learning in Mathematics Instruction. This quasi-experimental research was intended to know the effectiveness of group learning in matematics instruction. The subjects were the 1st graders of SLTP 12 Banjarmasin, South Kalimantan assigned to an experimental group and a control group. Data were gathered using test and documentary study, and were then analyzed by t-test. It could be concluded from data analyses that there was a difference in learning outcomes between students attending group learning and those not attending group learning.